Designing and implementing equity-based pandemic preparedness and response learning modules: lessons from a multi-country short-course. Issue 1 (31st December 2022) - Manzi, Anatole; Henley, Phaedra; Lieberman, Hannah; Topper, Langley; Wuethrich, Bernice; Logan, Jenae; Bekele, Abebe; Mubiligi, Joel; Davis, Sheila; Binagwaho, Agnes; Farmer, Paul; Mukherjee, Joia
ABSTRACT: Background: The COVID-19 pandemic has had disproportionate impacts across race, social class, and geography. Insufficient attention has been paid to addressing the massive inequities worsened by COVID-19. In July 2020, Partners In Health (PIH) and the University of Global Health Equity (UGHE) delivered a four-module short course, 'An Equity Approach to Pandemic Preparedness and Response: Emerging Insights from COVID-19 Global Response Leaders.' Objective: We describe the design and use of a case-based, short-course education model to transfer knowledge and skills in equity approaches to pandemic preparedness and response. Methods: This course used case studies of Massachusetts and Navajo Nation in the US, and Rwanda to highlight examples of equity-centered pandemic response. Course participants completed a post-session assessment survey after each of the four modules. A mixed-method analysis was conducted to elucidate knowledge acquisition on key topics and assess participants' experience and satisfaction with the course. Results: Forty-four percent of participants identified, 'Immediate need for skills and information to address COVID-19' as their primary reason for attending the course. Participants reported that they are very likely (4.75 out of 5) to use the information, tools, or skills from the course in their work. The average score for content-related questions answered correctly was 82–88% for each session. Participants ( 70-90%) said their understanding was Excellent or Very Good for each session. Participants expressed a deepened understanding of the importance of prioritizing vulnerable communities and built global solidarity. Conclusion: The training contributed to a new level of understanding of the social determinants of health and equity issues surrounding pandemic preparedness and response. This course elucidated the intersection of racism and wealth inequality; the role of the social determinants of health in pandemic preparedness and response; and the impacts of neocolonialism on pandemic response in low- and middle-income countries.